1971
DOI: 10.1111/j.1432-1033.1971.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Pig Skin Dermatan Sulfate

Abstract: The presence of sulfated uronic acid residues in dermatan sulfate has been known for some time. I n view of the copolymeric nature of pig skin dermatan sulfate, it was of interest to see whether the extra sulfate groups were attached to iduronic acid or glucuronic acid residues.Hyaluronidase-degraded dermatan sulfate was fractionated on Dowex-1 to yield fractions of varying sulfate content. It was observed that the degree of sulfation was inversely proportional to the glucuronic acid content. Oversulfated derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
3

Year Published

1973
1973
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 11 publications
1
23
0
3
Order By: Relevance
“…End-group analyses of the two preparations indicated that the low-molecular-weight preparation (II: 2-25-H-40) was enriched in non-reducing terminal fragments, compared with the high-molecular-weight preparation. In agreement with the observation that nonreducing terminal fragments are generally oversulphated (Malmstrom & Fransson, 1971), the sulphate/hexosamine molar ratio of preparation II: 2-25-H-40 was higher than that ofthe high-molecularweight preparation. Finally, oligosaccharides ranging from disaccharide to hexadecasaccharide were also used in the present study (Fransson & Roden, 1967b).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…End-group analyses of the two preparations indicated that the low-molecular-weight preparation (II: 2-25-H-40) was enriched in non-reducing terminal fragments, compared with the high-molecular-weight preparation. In agreement with the observation that nonreducing terminal fragments are generally oversulphated (Malmstrom & Fransson, 1971), the sulphate/hexosamine molar ratio of preparation II: 2-25-H-40 was higher than that ofthe high-molecularweight preparation. Finally, oligosaccharides ranging from disaccharide to hexadecasaccharide were also used in the present study (Fransson & Roden, 1967b).…”
Section: Resultssupporting
confidence: 89%
“…The resulting fragments which comprise the Liduronic acid-containing regions range from tetrasaccharide (molecular weight approximately 1000) to polysaccharides almost as long as the original polymer. In a previous study it was shown that long fragments (molecular weight 15000) derived from the non-reducing terminal portion of the chain were significantly oversulphated (Malmstrom & Fransson, 1971). Approximately 40% of the oversulphated material was represented by L-iduronic acid sulphatecontaining oligosaccharides (Fransson et al, 1974b).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the absence of PAPS, the epimerization reaction in the nonsulfated chondroitin is reversible and reaches a particular equilibrium state, where the D-gluco configuration dominates over the L-ido configuration (61). The degree of interconversion to IdoUA is much lower than actual IdoUA contents observed in native DS (62). A marked 4-O-sulfation modification of dermatan has been observed using human skin fibroblast microsomes as an enzyme source (29).…”
Section: Discussionmentioning
confidence: 88%
“…The radioactive product was identified as inorganic sulphate by paper chromatography. Other workers (Suzuki et al, 1968;Lindahl and Axelsson, 1971;Malmstrom and Fransson, 1971) Action of the Hunter corrective factor results in the disappearance of some 'oversulphated' areas (about one-third), and it was concluded that since the sulphate residue unique to such areas is that linked to L-iduronic acid, the sulphatase is for sulphated iduronic acid. This was confirmed using the disaccharide 4-O-a-sulphoiduronosyl-D-sulphoanhydromannose as substrate and measuring iduronic acid released by the combined action of Hunter factor and a-L-iduronidase.…”
mentioning
confidence: 99%